THE 1886 CIOMAS PEASANT COLLECTIVE ACTION: POLITICAL IMPACT TOWARDS THE DUTCH INDIES GOVERNMENT - Iskandar, Mohamad (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2009)
Ciomas in this study is an area located in the slope of Gunung Salak, Bogor regency (Buitenzorg) (Besluit. No. 7 year 1882). During the administration of Governor General Herman Willem Daendels, the northern part of this area had been sold to a private party, with the status of the land as private. The extent of the area was about 9.000 bau or approximately 7.220 ha (1 bau = 0,8 ha). As the consequence of the status, the governmentâ€™s authority over the land in Ciomas became limited compared to the authority over the governmentâ€™s land. On the other hand, the authority of the private land (landeigenar) owner of Ciomasâ€”who was called the landlord (landheer), over the local inhabitant was â€˜almostâ€™ unlimited. According to the regulation of the private land, the land owner has special rights, which was usually held by the government.Â In the colonial archive, the land owner was called â€œlandlordâ€ by the people and the government. It is different from the concept of landlord in the time Western Europe feudalism. However, in certain terms, there are similarities, including the special rights. This can be understood, regarding that Netherland who gave birth to VOC, was a feudal country.